Advancing rural science education in Chile through local rural knowledge: a design-based approach to water education - Iturbe-Sarunic, Catalina; Miller, Brant G.; Merino, Cristian (Frontiers in Education, 2025)
This study addresses the advancement of rural science education (RSE) through a focus on water education in Chile’s Los Lagos Region. Employing a Design-Based Research approach with four rural communities, the research first aimed to characterize local rural knowledge (LRK) and identify educational needs regarding local water sources, quality, and infrastructure challenges. Second, it focused on the collaborative co-design with teachers of a contextually relevant teaching and learning sequence (TLS) for water education. The developed TLS emphasizes water quality and utilizes a Place-Based Inquiry for Modeling approach, encouraging students to engage in authentic inquiry using sensor technology to gather and analyze real-time data about their local water. This process integrates LRK with national science standards in Chile to enhance students’ understanding and participation in water-related issues. The study underscores the critical importance of local contexts, community involvement, and participatory design in creating effective RSE. Findings have implications for educators, researchers, and curriculum designers seeking to integrate place-based learning, technology, and LRK in rural educational settings.